(untitled) (Colombia Medica, 2020)
Damage control resuscitation should be initiated as soon as possible after a traumatic event to avoid metabolic decompensation and high mortality rates. This article aims to assess the position of the Trauma and Emergency Surgery Group (CTE) from Cali, Colombia regarding prehospital care, and to present our experience in the implementation of the “Stop the Bleed” initiative within Latin America. Prehospital care is phase 0 of damage control resuscitation. Prehospital damage control must follow the guidelines proposed by the “Stop the Bleed” initiative. We identified that prehospital personnel has a better perception of hemostatic techniques such as tourniquet use than hospital providers. The use of tourniquets is recommended as a measure to control bleeding. Fluid management should be initiated using low volume crystalloids, ideally, 250cc boluses, maintaining the principle of permissive hypotension with a systolic blood pressure range between 80- and 90-mm Hg. Hypothermia must be managed using warmed blankets or the administration of intravenous fluids warmed before infusion. However, these prehospital measures should not delay the transfer time of a patient from the scene to the hospital. To conclude, prehospital damage control measures are the first steps in the control of bleeding and the initiation of hemostatic resuscitation in the traumatically injured patient. Early interventions without increasing the transfer time to a hospital are the keys to increase the survival rate of severe trauma patients.